Exploring athletes' perceptions of the relationship between mental toughness and dispositional flow in sport. (November 2016) - Jackman, Patricia C.; Swann, Christian; Crust, Lee
Abstract: Objectives: Despite considerable scholarly attention over the last two decades, little is known about the influence of dispositional attributes on flow in sport. In achievement settings, mental toughness (MT) is a personal capacity supporting the process of high performance. Based on common overlaps with peak performance, confidence, control, concentration, and thriving in demanding situations, the present research aimed to explore the relationship between MT and dispositional flow and elucidate the psychological variables underlying dispositional flow. Design: A mixed method explanatory participant-selection design was adopted, whereby a quantitative approach was used to identify individuals for a qualitative follow-up phase to explore the relationship between MT and dispositional flow. Method: An intensity sampling strategy was used to identify individuals with higher/lower MT and dispositional flow. Semi-structured interviews were conducted with 16 athletes ( M age = 25, SD = 3.24; female n = 10; male n = 6). An inductive content analysis was undertaken to interpret data. Results: Seven general dimensions describing the psychological attributes related to dispositional flow in athletes with higher and lower MT emerged. Specifically, differences in confidence, perfectionism, goal orientation, coping mechanism selection, locus of control, optimism and concentration were apparent and could account for differences in dispositional flow. Conclusion: While all athletes experienced flow, there were differences in dispositional flow and the processes involved in entering, maintaining and restoring flow between higher and lower MT subgroups. Findings are discussed in relation to the existing literature, and recommendations for future research into the MT-flow relationship are outlined. Highlights: A mixed method design was employed to explore the relationship between MT and dispositional flow. A quantitative assessment was used to identify individuals with higher/lower mental toughness and dispositional flow for follow-up interviews. An amalgam of psychological variables influencing dispositional flow emerged. These included concentration, confidence, coping mechanisms, goal orientation, locus of control, optimism and perfectionism. Differences between subgroups regarding dispositional flow emerged, which are described.